Interpretation of the problem in the Holy Quran an applied study on verses from the first part of Surat Al- Baqarah - Algzawi, Sana Hussien (Arab Journal for Sciences and Research Publishing, 2022)
This research highlights a very important and dangerous issue, named (the problem in the verses of the Holy Quran). Some skeptics used this issue to try and question the validity of our Holy Quran, so this study was a building bone in the world of qur’anic studies, in which the researcher collected the verses that gives an illusion of the occurrence of a problem and compare similar verses and then answer the problem in a logical scientific way. This way will be Judged upon the argument, proof and the Arabic language (the language of the Holy Quran) and based on the judges of the scientist of this field.The study concluded that the problem is what makes the illusion of a contradiction between the verses, and the reader may fall into something that illusions a problem in the verses and is not in reality, and this is only due to the shortness of our understanding or our inability to direct it, as the Holy Qur’an is innocent of the existence of a contradiction or conflict in it, it is a revelation The wise, the praiseworthy, falsehood does not come to him from before him or from behind him.
Keywords: The Problematic; The Similarities; The Holy Quran